2018
DOI: 10.1016/j.ajic.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of long-term-care facility onset Clostridium difficile infections in 10 US geographic locations during 2011-2015

Abstract: During 2011-2015, the adjusted long-term-care facility onset Clostridium difficile infection incidence rate in persons aged ≥65 years decreased annually by 17.45% (95% confidence interval, 14.53%-20.43%) across 10 US sites. A concomitant decline in inpatient fluoroquinolone use and the C difficile epidemic strain NAP1/027 among persons aged ≥65 years may have contributed to the decrease in long-term-care facility-onset C difficile infection incidence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Given that ribotype 027 strains are now endemic in healthcare settings, our data suggest that fluoroquinolones might not be as important of a CDI risk factor as before considering the recent changes in CDI epidemiology 21. A recent article published in 2017 demonstrated that a concomitant decline in inpatient fluoroquinolone use and the NAP1/027 strain may have contributed to the decrease in the incidence rate of long-term-care facility-onset CDI from 2011 to 2015 22. Our results from the Cochran-Armitage Trend Test also indicated that there was a trend of decrease in CDI risk with fluoroquinolones from 2004 to 2017.…”
Section: Discussionmentioning
confidence: 81%
“…Given that ribotype 027 strains are now endemic in healthcare settings, our data suggest that fluoroquinolones might not be as important of a CDI risk factor as before considering the recent changes in CDI epidemiology 21. A recent article published in 2017 demonstrated that a concomitant decline in inpatient fluoroquinolone use and the NAP1/027 strain may have contributed to the decrease in the incidence rate of long-term-care facility-onset CDI from 2011 to 2015 22. Our results from the Cochran-Armitage Trend Test also indicated that there was a trend of decrease in CDI risk with fluoroquinolones from 2004 to 2017.…”
Section: Discussionmentioning
confidence: 81%
“…proportions of different antibiotic classes among all oral antibiotics prescribed in the outpatient setting in the US are notably different from the corresponding proportions in England (compare Table 2 with Table 6). Those differences, particularly for fluoroquinolones and cephalosporins may be related to differences in the rates of severe bacterial infections, particularly Clostridium difficile (C. difficile) infections between the two countries [42], with reduction in fluoroquinolone and cephalosporin prescribing found to be associated with reduction in the incidence of C. difficile infection in both countries [43,44]. Table 4).…”
Section: Usmentioning
confidence: 99%
“…14 Several recent studies, including that by Reveles et al, that document a decline in HCF CDI include patients of any age, usually adults aged 18 years and older. [13][14][15][22][23][24][25] As such, HCF CDI accounts for most episodes identified, ranging from 65% to 89% for those that defined both HCF and community-associated CDI. Declines in overall incidence, therefore, are not unexpected in populations for which the majority of episodes are HCF CDI, nor are comparisons between this study and those published contradictory; rather, our findings suggest trends in disease burden among those of younger age might differ from those of older age.…”
Section: Discussionmentioning
confidence: 99%